Companionship in the spirit. A history of the spirituality of the Society of Jesus - García de Castro Valdés, SJ, José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
One of the most unique features of Ignatian Spirituality is the development of a loving gaze on all things, on all Creation, starting with a merciful and unconditional acceptance of the person who prays. «God labors and works for me in all creatures» [Sp Ex 236]. Throughout its 475 years of history, the Society of Jesus has been present in very different places and very diverse circumstances, a kind of presence that employs action as a principal means to explain her religious experience, her particular way of loving God and loving the neighbor: «Love ought to manifest itself more by deeds than by words» [Sp Ex 230]. This article offers an inescapable panoramic view of the kind-hearted and merciful work that the Society of Jesus, the Jesuits who have dwelt in her and her collaborators, have been doing through her History.